PENGELOLAAN SAMPAH RUMAH TANGGA DENGAN KOMPOSTER KALENG BEKAS UNTUK MENDUKUNG PENGEMBANGAN DESA WISATA DI DESA DARA KUNCI KECAMATAN SAMBELIA KABUPATEN LOMBOK TIMUR - Awwalin, Muhamad Zainul Fajri; Istiqamah, Juhratul; Rahmat, Solihin; Utami, Wiwin; Nida, Holizatun; Dewi, Denisa Kartika; Novansyah, Rizky; Hurnah, Hurnah; Kahfi, Ahmad Sohibul; Suartika, I Made (Universitas Mataram, 2024)
Household waste management is an important aspect of tourism development in Dara Kunci Village, Sambelia District, East Lombok Regency. Although the tourism potential of Dara Kunci Village holds great promise for boosting the local economy, its development is still in its early stages and requires careful preparation. One aspect that needs attention is waste management, which is a crucial factor in maintaining the beauty and cleanliness of tourist environments. Therefore, this activity aims to raise awareness among the community about the importance of waste management, and to introduce and implement a simple yet effective innovation, namely the use of recycled tin can composters, as an initial step in reducing household waste generation. The methods employed involve community awareness campaigns to promote environmental consciousness, training sessions on compost production using recycled tin can composters as a solution for household waste management systems, and providing guidance on compost production at home as a sustainable solution to reduce household waste generation. The results of this activity demonstrate an increase in knowledge and skills among the residents of Dara Kunci Village in managing household waste, resulting in the production of liquid organic fertilizer and compost. Although not all composts meet the desired maturity criteria, this activity provides valuable insights for the community into the composting process and the importance of patience in achieving optimal results